Integrated prevention of mother-to-child HIV transmission services, antiretroviral therapy initiation, and maternal and infant retention in care in rural north-central Nigeria: a cluster-randomised controlled trial. Issue 5 (May 2016) - Aliyu, Muktar H; Blevins, Meridith; Audet, Carolyn M; Kalish, Marcia; Gebi, Usman I; Onwujekwe, Obinna; Lindegren, Mary Lou; Shepherd, Bryan E; Wester, C William; Vermund, Sten H
Summary: Background: Antiretroviral therapy (ART) and retention in care are essential for the prevention of mother-to-child HIV transmission (PMTCT). We aimed to assess the effect of a family-focused, integrated PMTCT care package. Methods: In this parallel, cluster-randomised controlled trial, we pair-matched 12 primary and secondary level health-care facilities located in rural north-central Nigeria. Clinic pairs were randomly assigned to intervention or standard of care (control) by computer-generated sequence. HIV-infected women (and their infants) presenting for antenatal care or delivery were included if they had unknown HIV status at presentation (there was no age limit for the study, but the youngest participant was 16 years old); history of antiretroviral prophylaxis or treatment, but not receiving these at presentation; or known HIV status but had never received treatment. Standard of care included health information, opt-out HIV testing, infant feeding counselling, referral for CD4 cell counts and treatment, home-based services, antiretroviral prophylaxis, and early infant diagnosis. The intervention package added task shifting, point-of-care CD4 testing, integrated mother and infant service provision, and male partner and community engagement. The primary outcomes were the proportion of eligible women who initiated ART and the proportion of women and their infants retained in care at 6 weeks and 12 weeks post partum (assessed by generalised linear mixed effects model with random effects for matched clinic pairs). The trial is registered withClinicalTrials.gov, numberNCT01805752 . Findings: Between April 1, 2013, and March 31, 2014, we enrolled 369 eligible women (172 intervention, 197 control), similar across groups for marital status, duration of HIV diagnosis, and distance to facility. Median CD4 count was 424 cells per μL (IQR 268–606) in the intervention group and 314 cells per μL (245–406) in the control group (p<0·0001). Of the 369 women included in the study, 363 (98%) had WHO clinical stage 1 disease, 364 (99%) had high functional status, and 353 (96%) delivered vaginally. Mothers in the intervention group were more likely to initiate ART (166 [97%] vs 77 [39%]; adjusted relative risk 3·3, 95% CI 1·4–7·8). Mother and infant pairs in the intervention group were more likely to be retained in care at 6 weeks (125 [83%] of 150 vs 15 [9%] of 170; adjusted relative risk 9·1, 5·2–15·9) and 12 weeks (112 [75%] of 150 vs 11 [7%] of 168 pairs; 10·3, 5·4–19·7) post partum. Interpretation: This integrated, family-focused PMTCT service package improved maternal ART initiation and mother and infant retention in care. An effective approach to improve the quality of PMTCT service delivery will positively affect global goals for the elimination of mother-to-child HIV transmission. Funding: Eunice Kennedy Shriver National Institute of Child Health and Human Development and US National Institutes of Health.